Processo de juvenilização da educação de jovens e adultos entre os anos de 2000 e 2019: um estudo na Escola Joaquim Braz Pereira - município de Sobrado/PB - Luna, Edno Paulino de (2021)
This study is focused on the dialogue on the process of youthization of Youth and Adult Education (EJA) in the early decades of the millennium (2000 to 2019), with the public school system of the municipality of Sobrado, in the Zona da Mata paraibana and the respective students of elementary school II of the EJA modality as subjects of the research. To this end, we set the following objectives: to outline a critical analysis of the history of the EJA in the Brazilian context; to list the data collected in the minutes of the Joaquim Braz Pereira School (EJBP), Elementary School II in the last 20 years (2000-2019) and, finally, to make considerations about the actions of the municipal management of the EJA. Taking as a reference to perform and analyze this study the theoretical- and comprehensive contributions of popular education in Brazil In this direction, we present a case study inserted in the frame of reference of Marxian critical theory, with documentary approach from the reading of the minutes of the school referenced as an essential sample of a context, also directed by the objectives. Even facing the difficulties caused by the COVID-19 pandemic, this research demonstrated that the whole process of juvenilization that occurred in the EJA comprises a phenomenon that permeates historical moments, conjunctures, with strong influences of what we can call local social conditions that we can highlight: demand, housing, income and work.